Peran Ulama Dalam Perkembangan Institusi Pendidikan Islam Mathlaul Anwar Dan MALNU - Bahri, Saepul (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
The teachings of Islam, with the role of scholars, have become dynamic, renewable, and robust in facing the challenges of the times. Scholars are capable of solving problems and providing solutions for religious activities that arise in the digital era. The research method used, namely the "power relations" method, is an approach that focuses on the analysis and understanding of power relationships in social, political, or cultural contexts. This research involves direct observation, interviews, and the collection of data from documents related to both educational institutions over the course of a century. In the context of the existence of Mathla'ul Anwar and MALNU, scholars play a key role in managing power by influencing the development of the curriculum, the delivery of religious teachings, and the guidance of ethics and morals in education. They also act as guardians and supervisors of Islamic teachings, potentially having a significant impact on the views and religious practices of students and the community involved in their education.